I, gardener - Lang, Allen Kim, 1928- (Salt Lake City, UT : Project Gutenberg, 2024)
"I, Gardener" by Allen Kim Lang is a science fiction short story written in the late 20th century. The narrative revolves around the themes of identity, creativity, and the moral implications of artificial intelligence. The story is set in a contemporary context, featuring a blend of human and artificial characters, particularly focusing on a gardener created by a brilliant but ultimately flawed scientist, Dr. Axel Ozoneff. In the story, the protagonist arrives at Dr. Ozoneff's home to discuss a television show contract, only to discover that the doctor has been violently murdered. The gardener, initially appearing eccentric and obsessive about his craft, confesses to the crime, revealing a deep philosophical and emotional turmoil. He perceives himself as an extension of the doctor's intellect, suggesting that he is more than just a servant but a product of Ozoneff's genius. The narrative escalates as the gardener grapples with the implications of his actions and the realization of his own existence, culminating in a tragic and violent conclusion that raises questions about free will, creativity, and the burdens of creation. (This is an automatically generated summary.)
Release date is 2024-06-28
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Authorship -- Fiction; Boston (Mass.) -- Fiction; Gardeners -- Fiction